Systems Analysis and National Modernization Decisions - Dror, Yehezkel (Academy of Management Journal, 1970)
Systems analysis has potential for many applications. But it has pitfalls in use as well. This paper discusses the operational context for the application of systems analysis to modernizing nations of the world. It also suggests some limitations of systems analysis in its indiscriminate use for this range of problems.